1995
DOI: 10.1346/ccmn.1995.0430309
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Mechanisms of Imazamethabenz-Methyl on Homoionic Montmorillonite

Abstract: Almtraet --The adsorption of the herbicide imazamethabenz-methyl, a mixture of the two isomers methyl (_+)-2-[4,5-dihydro-4-methyl-4-(1 -methylethyl)-5-oxo-1H-imidazol-2-yl]-4-methylbenzoate (para isomer) and methyl (+_)-2-[4,5-dihydro-4-methyl-4-(1 -methylethyl)-5-oxo-1H-imidazol-2-yl]-5-methylbenzoate (meta isomer), from water onto AP +-, Fe 3+-, Ca 2+ -, K +-and Na+-montmorillonite was studied by analytical (HPLC) methods. The adsorption from an organic solvent was also investigated by spectroscopic (IR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…Nevertheless, the concentration was probably below the limit of detection to show any trace of residual or sorbed MCPA on the soil. In contrast to Pusino et al ( 1995 ), the adsorbed herbicide could not be detected with FTIR. Yet, the most prominent features of the spectra of both pure MCPA and soils can be distinguished, i.e., the bands of carboxylic and carbonyl groups are located around 1,745 cm −1 (MCPA dimer) and 1,710 cm −1 (monomer), and 1,650 cm −1 in soils.…”
Section: Resultscontrasting
confidence: 94%
“…Nevertheless, the concentration was probably below the limit of detection to show any trace of residual or sorbed MCPA on the soil. In contrast to Pusino et al ( 1995 ), the adsorbed herbicide could not be detected with FTIR. Yet, the most prominent features of the spectra of both pure MCPA and soils can be distinguished, i.e., the bands of carboxylic and carbonyl groups are located around 1,745 cm −1 (MCPA dimer) and 1,710 cm −1 (monomer), and 1,650 cm −1 in soils.…”
Section: Resultscontrasting
confidence: 94%
“…Similarly, in sorption studies on NACs, significantly more sorption occurred on smectites exchanged with weakly hydrated monovalent cations (i.e., Cs + and K + ) relative to more strongly hydrated divalent cations (e.g., Ca 2+ ). The preference of organic solutes for K-over Ca-saturated clays has also been observed for thiazaluron (40), imazamethabenz-methyl (41), and the nitroaromatic compounds dinitro-o-cresol and dinoseb (19). For the NACs, FTIR spectra of the clay-organic complexes showed that the -NO2 groups interacted directly with weakly hydrated exchangeable cations (i.e., K + and Cs + ) (18,20,33).…”
Section: Resultsmentioning
confidence: 76%
“…HPLC Analyses. The concentrations of IMZM and IMZA were determined by HPLC (Pusino et al, 1995). A Waters 510 liquid chromatograph, equipped with a 250 × 4 mm i.d.…”
Section: Methodsmentioning
confidence: 99%